(untitled) (Praxis Educativa, 2020)
The study focused its object on the crossing of the new discursive modalities (NMD), understood as those specific interactions of the educational fact that arise from current communicative needs, and the forms of pedagogical intervention in the university institution. The general objective was to analyze the NMD and its link / tension with the forms of pedagogical intervention, through the identification and description of the communicative interactions. The critical analysis of discourse from the perspective of Teun van Dijk was the adopted methodology and for the collection of data, teacher interviews and student narratives were used as instruments. Among the emerging categories are: ICT as democratizing knowledge, teaching styles, affective conceptions in the educational event, stages of teacher socialization and education and diversity.